MANTRA TETULUNGAN: STRUCTURE AND MEANING REVIEW - Sariasih, Yanti (JURNAL KONFIKS, 2025)
Mantra is a part of oral literature that is still commonly found in the lives of Indonesian people. The Tetulungan Mantra is one of the Javanese mantras that is still sustainable in the life of the people of the village of Cahaya Mas. This research was conducted to describe the structure and meaning of the Tetulungan mantra in the life of the Javanese people of Cahaya Mas village, Mesuji Makmur district. This research is a type of field research conducted using a qualitative descriptive method. The research data is in the form of quotations of words or sentences contained in the Tetulungan mantra. Mantras are obtained through an interview process conducted with elders who master the Tetulungan spell. After all the data is sufficient, then the analysis process is carried out using interactive techniques. The results of the research show that the Javanese mantra has the main function of rejecting various logs, calamities, calamities, and all the suffering that can come in human life. The spell has a unique structure compared to the structure of spells in general. Successively, the structure of the Tetulungan mantra includes opening, aim, suggestion, and closing elements. The mantra begins with the remembrance of Allah and ends with complete submission to Allah, the one who has power over all things. It also shows that the Tetulungan spell can only be recited by people who believe in Islam as their religion. In addition, the Tetulungan mantra also contains a very deep meaning regarding belief in God's power, submission to God, and the human perspective on God's creation.